Determinants of repayment performance in microfinance programs in Malaysia: The case of Tekun Nasional programs - Norhaziah, Nawai (2014)
The objective of this study is to assess the potential factors influencing micro entrepreneur’s repayment performance in microfinance programs in Malaysia by developing a model of repayment performance. The study chooses TEKUN Nasional (TN) microfinance programs as a case study. The research framework of this study is built by four factors namely individual/borrower factors, firm/business factors, loan factors and institutional/lender factors. The study used mixed methodology, combining between quantitative and qualitative data through survey questionnaire and in depth interviews. However, the main study is based on quantitative data and supported by qualitative data. The analysis began with a descriptive exploration, followed by multinomial logit regression analysis and content analysis. Data were collected using multi stage random sampling in Peninsular Malaysia. 401 microentrepeneurs were selected as a sample for quantitative data and 21 microentrepreneurs and 6 TN State managers were selected for qualitative data. The results show that in terms of individual/borrower characteristics, only micro entrepreneur’s religious education level is statistically significant in the relationship between delinquent and good borrowers and between default and good borrowers. Whereas, in firm/business characteristics, the result shows that distance, business formality and total sales are statistically significant. The finding shows that total loan received, loan type and repayment schedule are the loan characteristics that affect micro entrepreneur’s loan repayment. In terms of institutional/lender characteristics, the finding shows that loan monitoring is statistically significant in the relationship between delinquent and good borrowers. This study contributes significantly to the knowledge of microfinance program at large, wherein it explains that repayment performance plays an important role to ensure that MFIs can continue providing microfinance to the micro entrepreneurs without depending on subsidies